ANALYSIS OF THE APPLICATION OF COMPUTER TECHNOLOGIES IN THE ECONOMIC ANALYSIS OF A BUSINESS ENTITY - PROSKUROVYCH, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The rapid digital transformation of the economy has significantly increased the role of computer technologies in economic analysis. Modern analytical tasks require the use of advanced software, business analytics systems and big data processing tools to increase the accuracy, speed and completeness of decision-making processes. Therefore, the use of computer technologies in the economic analysis of a business entity is one of the most relevant areas of development of both economic science and management practice. They allow significantly increasing the speed, accuracy and objectivity of analytical calculations, expanding the range of studied indicators, as well as visualizing the results for making more informed management decisions. The article considers the role and importance of computer technologies in increasing the efficiency of economic analysis in the conditions of digital transformation of the economy. The possibilities of using specialized software, business analytics systems and big data processing tools for comprehensive research of economic processes and the formation of informed management decisions are analyzed. The leading components of the analytical work of an entrepreneurial entity and the directions of analytical solutions in the era of digitalization are outlined. The software products used in the process of computerization of economic analysis are characterized according to their functionality and scope of application: BI systems and analytical platforms, integrated ERP systems, platforms for Big Data and machine learning, cloud analytical services. Particular attention is paid to the implementation of cloud services and intelligent algorithms that ensure the flexibility of analytical systems, reduce information processing time and increase the level of visualization of results. The importance of automated methods of data quality control and standardization of analysis procedures as tools for reducing the probability of errors and increasing the reliability of results is substantiated. The main problems of the process of computerization of analytical work and ways to solve them are outlined. It is proven that computer technologies act as a strategic resource for the modernization of management systems and ensure the competitiveness of enterprises in the conditions of the digital economy. The results of the study show that the integration of computer technologies allows for a comprehensive analysis of economic processes, promotes accurate forecasting and reduces the likelihood of errors due to automated data verification. Cloud solutions and intelligent algorithms significantly improve analytical flexibility, scalability and availability of information in real time. Standardization of analytical procedures ensures consistency and reliability of interpretation of results. The introduction of computer technologies not only optimizes the technical aspects of economic analysis, but also acts as a strategic driver for the modernization of the management system. Business entities that effectively integrate such technologies strengthen their competitiveness and adaptability in the digital economy.
Keywords: economic analysis; computer technology; business analytics; cloud services; big data; digital economy; automation